On the physical layer security characteristics for MIMO-SVD techniques for SC-FDE schemes - Madeira, João (2019)
partially supported by the FCT -Fundacao para a Ciencia e Tecnologia and Instituto de Telecomunicacoes under projects UID/EEA/50008/2019. PES3N POCI-01-0145-FEDER-030629.